POLITICAL THEORY’S IMAGINATION. A FEW REMARKS ON WIKTOR MARZEC BOOK - Ozimek, Magdalena (Society Register, 2017)
Social sciences, understood as critical and not neutral by nature, they should be equipped with specific competencies and sensivity. C. W. Mills these comptence define as sociological imagination – which is study of the relationship of history and biography, Giddens interpreted it as three basic senses: historical, anthropological, critical. The translation into political science would be a political theories imagination, it consist, among over things like a: historicity of political phenomena, antisubstansialism, research self-awareness. Definition of political theories imagination I propose in the context of Wiktor Marzec’s paper Rebelion and Reaction, which is a study from field of historical sociology, it’s in itself a lot of inspiration for theorists of politics: research, theoretical and methodological. It is worth considering – in this context – fundamental categories of political science, like political subjectivity and the political, also revalidate in their range.